2019
DOI: 10.1200/jop.19.00077
|View full text |Cite
|
Sign up to set email alerts
|

“You Have to Keep a Roof Over Your Head”: A Qualitative Study of Housing Needs Among Patients With Cancer in New York City

Abstract: PURPOSE: Housing status can become compromised in the wake of financial hardship for some patients with cancer and become a source of disparity. This qualitative study describes the types of housing issues experienced by patients with cancer and survivors of cancer in New York City. METHODS: Semistructured interviews were conducted with a volunteer sample of 21 patients with cancer or survivors of cancer treated in New York City who reported housing needs in the period after diagnosis through survivorship. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Some of our participants were homeowners, and as household income is affected by cancer-related income and/or job loss, home maintenance, taxes, and mortgage payments may become difficult for low-income cancer patients to afford. In a qualitative study of cancer patients and survivors with housing needs, the participants who had been homeowners when they commenced treatment had lost their homes to foreclosure after falling behind on mortgage payments [2]. Potentially burdensome housing costs and home loss, and the stress they entail, could be contributing factors to food insecurity among renters and homeowners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of our participants were homeowners, and as household income is affected by cancer-related income and/or job loss, home maintenance, taxes, and mortgage payments may become difficult for low-income cancer patients to afford. In a qualitative study of cancer patients and survivors with housing needs, the participants who had been homeowners when they commenced treatment had lost their homes to foreclosure after falling behind on mortgage payments [2]. Potentially burdensome housing costs and home loss, and the stress they entail, could be contributing factors to food insecurity among renters and homeowners.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income, immigrant, and minority cancer patients, for whom a cancer diagnosis can be an extreme financial burden added to an already financially precarious situation [1], can be particularly affected by poor housing conditions and food insecurity [2]. Adequate housing and food are two fundamental human rights and are essential contributors to health [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients experiencing homelessness often have other concerns besides health care, such as housing, transportation, and childcare. 63,64 Programs that address barriers to care, such as transport vouchers, and provide access to basic needs, such as food, shelter, and safety, can allow patients to direct more of their time and energy toward their health care needs.…”
Section: Community and Regional Interventions For Patients Experiencing Homelessnessmentioning
confidence: 99%
“…A recently reported survey of cancer patients in New York City showed that housing needs across six categories (cost, home loss, stability, conditions, accessibility, and safety) were often interrelated and emerged both before and after a cancer diagnosis. 1 A study of primary care patients found that 40 percent had food insecurity. 2 These studies highlight the need to ensure that we are asking the right questions of our patients.…”
mentioning
confidence: 99%